Serum concentration of thyroxine and triiodothyronine in newborn calves from cows supplemented with barium selenate - Víctor R. Leyán; Ricardo H. Chihuailaf; Fernando G. Wittwer (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Barium selenate is an inorganic source of selenium (Se) used in prolonged-release preparations to treat selenium deficiency in bovines. Objective: To evaluate serum concentrations of triiodothyronine (T3) and thyroxine (T4) hormones in newborn calves from mothers supplemented with barium selenate during prepartum. Methods: Six black Frisian pregnant cows were supplemented with barium selenate subcutaneously during the last two months of gestation, until calving. Six cows were used as controls. All cows were subjected to a low Se diet, consisting of hay from natural pasture and commercial concentrate lacking Se. The Se balance was measured through the activity of erythrocyte glutathione peroxidase (GPx). Serum concentration of T3 and T4 in calves was determined by electrochemiluminescence. Results: Se supplementation during prepartum increased GPx activity in cows from day 45 post-supplementation (p<0.05). Calves from supplemented mothers showed higher average serum Se concentration than calves from non-supplemented mothers. The average concentration of T3 in the calves from supplemented mothers was lower in the first hour of life (p<0.05) compared with calves from mothers of the non-supplemented group. A decrease (p<0.05) in T4 serum concentrations was observed in both groups at seven days of age. Conclusions: Administration of barium selenate to cows during prepartum generates a reduction in serum concentration of T3 in the first hour of life of calves.